Engineering technology and industrial chemistry with applications - Haghi, Reza K.; Torrens, Francisco (Apple Academic Press, 2019)
"Key features: - explores the future of petroleum engineering, petrochemicals, and environmental and energy sustainability - presents new research on the electrospinning process - discusses the nanofiber production capability of the electro-centrifuge technique - examines several issues in chemical theory and computation - provides new research on a variety of topics in industrial chemistry and engineering technology - looks at important issues in polymers technology and science - provides several illustrative case studies"--Resumé vydavatele
Keywords: chemické inženýrství; chemická technologie; chemický průmysl; fyzikální chemie; chemical engineering; chemical technology; chemical industry; physical chemistry; sborníky; papers of several authors